Maqasid Al-Quran Approach Towards Understanding Jihadism and De-Radicalization - Tazul Islam (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
Jihad itself is not an objective in Islam. Yet, it is a means for various objectives like distinction between truth and false, gaining Allah's satisfaction, self-defence and repelling aggression. However, violent jihadism has become a source of extremism and radicalization. This research aims to dissolve the controversy aroused about implementations of jihad in contemporary era by confining its objectives. The use of Jihad, its usage and types may be determined based on its objectives. This research is qualitative in nature as it focuses only on library data. However, to explore a maqasid al-Quran perspective, books of tafsir will be used for the relevant issues. It comes out with a framework to understand jihadism and radicalization based on maqasid al-Quran.